A regenerative approach towards recovering the mechanical properties of degenerated intervertebral discs: Genipin and platelet-rich plasma therapies. (February 2017) - Nikkhoo, Mohammad; Wang, Jaw-Lin; Abdollahi, Masoud; Hsu, Yu-Chun; Parnianpour, Mohamad; Khalaf, Kinda
Degenerative disc disease, associated with discrete structural changes in the peripheral annulus and vertebral endplate, is one of the most common pathological triggers of acute and chronic low back pain, significantly depreciating an individual's quality of life and instigating huge socioeconomic costs. Novel emerging therapeutic techniques are hence of great interest to both research and clinical communities alike. Exogenous crosslinking, such as Genipin, and platelet-rich plasma therapies have been recently demonstrated encouraging results for the repair and regeneration of degenerated discs, but there remains a knowledge gap regarding the quantitative degree of effectiveness and particular influence on the mechanical properties of the disc. This study aimed to investigate and quantify the material properties of intact (N = 8), trypsin-denatured (N = 8), Genipin-treated (N = 8), and platelet-rich plasma–treated (N = 8) discs in 32 porcine thoracic motion segments. A poroelastic finite element model was used to describe the mechanical properties during different treatments, while a meta-model analytical approach was used in combination with ex vivo experiments to extract the poroelastic material properties. The results revealed that both Genipin and platelet-rich plasma are able to recover the mechanical properties of denatured discs, thereby affording promising therapeutic modalities. However, platelet-rich plasma–treated discs fared slightly, but not significantly, better than Genipin in terms of recovering the glycosaminoglycans content, an essential building block for healthy discs. In addition to investigating these particular degenerative disc disease therapies, this study provides a systematic methodology for quantifying the detailed poroelastic mechanical properties of intervertebral disc.